Thermal and geochemical investigation of ice wedges in northern Victoria Land (Antarctica) - RAFFI, Rossana; B. STENNI; O. FLORA; U. GENTILI (Terra Antartica Publication, 2008)
During the 1998-1999, 2000-2001 and 2003-2004 field seasons, geomorphological surveys of permafrost-related polygons were carried out in northern Victoria Land. Widespread diffusion of ice wedges was ascertained. The ice wedges were found at depths ranging from 10 cm to 74 cm from the ground surface. Their size ranged from 5-7 cm to 155 cm in width, with an average of 49 cm at the top, and from 20 cm to over 150 cm in height, with an average of 85 cm. The wedge ice was milky-white in colour and largely free of sediment, with numerous oriented gas inclusions forming vertical foliations. A vertical open fissure, 2-5 mm wide and filled with small loose ice grains, was present at the centre of most ice wedges and extended down to the bottom of the wedge or to the bottom of the excavated section. The study investigated the thermal regime and stable-isotope composition of selected ice wedges. The aim was to establish whether thermal conditions trigger ice-wedge cracking and to define the processes which lead to the formation of wedge ice.